Effectiveness of Poedji Rochjati Score Card (PRSC) for Detecting High Risk in Pregnant Woman at Tegalwaru Community health Center Purwakarta - Perbawa, Prayudha Tegar; Verawaty, Verawaty (Syntax Literate, 2024)
Pregnancy, childbirth, postpartum, and infant care are natural physiological processes. However, there is a potential for a life-threatening situation to arise during this period, which can pose a risk to both the mother and the baby and, in severe cases, even lead to death. If we can effectively detect them, we can prevent maternal deaths. One tool to detect high-risk pregnant women is the Poedji Rochjati Score Card (PRSC). The aim of this research is to determine the effectiveness of the Poedji Rochjati Score Card (PRSC) for detecting high risk in pregnant women in the Purwakarta Community Health Center area, Purwakarta Regency. The study's research design was a retrospective cohort with secondary data. The Tegalwaru Community Health Center, Tegalwaru District, Purwakarta Regency hosted the research from December 2023 to January 2023. In 2022, all 920 pregnant women were included in this study. This study used total population techniques to sample. There were 617 respondents (67.1%) of low-risk pregnant women, 279 respondents (30.3%) with high-risk pregnancies, and 24 respondents (2.6%) with very high-risk pregnancies. Pregnant women with a score of 2 had 617 respondents (67.1%), 6 had 235 respondents (25.5%), 10 had 44 respondents (4.8%), 14 had 20 respondents (2.2%), and 18 had 4 respondents (0.4%). The Poedji Rochjati Score Card (PRSC) is effective for detecting high-risk pregnant women. Based on the results of the Chi Square test, the p value was <0.001. The Poedji Rochjati Score Card (PRSC) effectively identifies high-risk pregnancies, comprehensive care is still necessary for pregnancies without risk, as the risk of pregnancy can fluctuate throughout pregnancy and delivery.